2020
DOI: 10.3758/s13423-019-01692-9
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of the cognitive and perceptual factors influencing attentional scaling and visual processing

Abstract: An important mechanism used to selectively process relevant information in the environment is spatial attention. One fundamental way in which spatial attention is deployed is attentional scalingthe process of focusing attentional resources either narrowly or broadly across the visual field. Although early empirical work suggested that narrowing attention improves all aspects of visual processing, recent studies have demonstrated that narrowing attention can also have no effect or even a detrimental impact when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 114 publications
3
12
0
Order By: Relevance
“…While there have been claims that attentional breadth can be exogenously manipulated on shorter timescales (Benso et al, 1998;Mounts & Edwards, 2017), it is unclear how to reconcile these with the findings implying the process is more sluggish. It is likely that the differences in methodology are at least partly responsible for the different time estimates (for a review, see Lawrence, Edwards, Talipski, & Goodhew, 2020). For example, at least some of both Benso et al's (1998) and Mounts and Edwards' (2017) experiments likely compelled shifts of attention in addition to changes in the size of the attentional breadth.…”
mentioning
confidence: 99%
“…While there have been claims that attentional breadth can be exogenously manipulated on shorter timescales (Benso et al, 1998;Mounts & Edwards, 2017), it is unclear how to reconcile these with the findings implying the process is more sluggish. It is likely that the differences in methodology are at least partly responsible for the different time estimates (for a review, see Lawrence, Edwards, Talipski, & Goodhew, 2020). For example, at least some of both Benso et al's (1998) and Mounts and Edwards' (2017) experiments likely compelled shifts of attention in addition to changes in the size of the attentional breadth.…”
mentioning
confidence: 99%
“…Previous neurophysiological studies have shown that exogenous attention tends to affect ventral pathway in which more parvo cells are involved in processing, while endogenous attention tends to affect dorsal pathway in which more magno cells are involved in processing (Astafiev et al., 2003; Corbetta et al., 2000, 2005; Giesbrecht et al., 2003; Hopfinger et al., 2000; Kastner et al., 1999; Shulman et al., 1999, 2003). We suggest that the opposite effects of the two types of attention originate from the difference in the size of RFs across the two main visual pathways, since the RFs of parvo cells are known to be smaller than that of magno cells (Lawrence, Edwards, Talipski, & Goodhew, 2020). Exogenous attention activates more parvo cells with smaller RFs, thus increasing the perceived size of the attended stimulus, whereas endogenous attention activates fewer magno cells with larger RFs, thus decreasing the perceived size (see Figure 1).…”
Section: Discussionmentioning
confidence: 86%
“…Although congruent and incongruent flankers (Experiment 1) as well as the degree of contrast of the flankers compared with the target (Experiment 2) interact with the cultural background of the participants to differentially influence accuracy or reaction times, we cannot fully account for the pattern of results. We designed the experiment to test whether cultures differed in the resolution of information over space, based on the idea that Eastern cultures represent attended information at a lower resolution than Westerners do (Boduroglu & Shah, 2017); although lower representational resolution sacrifices detail, it makes it possible for attention to be distributed more broadly over space (Lawrence et al, 2020). Such ideas are consistent with Eriksen's zoom model (C. W. Eriksen & St James, 1986;C.…”
Section: Discussionmentioning
confidence: 94%
“…The question of whether cultural background can impact the resolution with which the visual environment is represented has gained substantial interest in recent years. Some studies have argued that culture can determine how broadly visual attention is allocated to the environment, thereby impacting the precision of representations (Boduroglu & Shah, 2017;Boduroglu, Shah, & Nisbett, 2009;Hakim, Simons, Zhao, & Wan, 2017;Lawrence, Edwards, Chan, Cox, & Goodhew, 2019;Lawrence, Edwards, Talipski, & Goodhew, 2020). For instance, Boduroglu and Shah (2017) demonstrated that East Asians performed more poorly than Americans on the functional field of view task, and, compared with Americans, their errors were less likely to be due to selecting a neighbor of the target.…”
mentioning
confidence: 99%